Adaptive routing of multiple taxis by mutual exchange of pathways. (18th December 2009) - Yamamoto, Kosuke; Uesugi, Kentaro; Watanabe, Toyohide
The tremendous development of information and communication technology has a large influence for service management in the taxi dispatching work. However, taxi drivers who want to drive in 'cruising taxis' decide their travel routes by depending on their own heuristics. As a result, traffic jams and local excess supplies have often been occurred. In this paper, we propose an adaptive routing method in the cruising taxis. In our method, pathways where many customers are expected to exist are assigned to drivers. This assignment adapts dynamically to carrying customers. Our simulation experiment shows that our method was able to pick up more customers than the existing means of cruising taxis.